2016
DOI: 10.4236/health.2016.85044
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between the Profile of Mood States (POMS) and the WHOQOL-26 among Japanese University Students

Abstract: In this study, we investigated six types of mood state (tension-anxiety, depression-dejection, anger-hostility, vigor, fatigue, and confusion) using the Profile of Mood States (POMS) with 40 Japanese university students. We examined five main quality of life (QOL) domains (physical health, psychological health, social relationships, and environmental health) using the World Health Organization Quality of Life Scale (WHOQOL-26). We also examined the total scale score. We examined Spearman's rank correlations be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
0
4
0
1
Order By: Relevance
“…For depression, three instruments were used to assess the outcomes: the Center for Epidemiologic Studies Depression Scale (CES-D) ( 32 ), the Hospital Anxiety and Depression Scale (HADS) ( 33 ), and the Profile of Mood States score (POMS) ( 34 ). We did subgroup analyses for the different instruments, and the meta-analysis showed that although the MD in the subgroup of the CES-D had no statistical significance (P=0.25), the total SMD showed statistical significance between the intervention and control groups [SMD, −0.62; 95% CI: (−1.20, −0.03); P=0.04; random-effects model] ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…For depression, three instruments were used to assess the outcomes: the Center for Epidemiologic Studies Depression Scale (CES-D) ( 32 ), the Hospital Anxiety and Depression Scale (HADS) ( 33 ), and the Profile of Mood States score (POMS) ( 34 ). We did subgroup analyses for the different instruments, and the meta-analysis showed that although the MD in the subgroup of the CES-D had no statistical significance (P=0.25), the total SMD showed statistical significance between the intervention and control groups [SMD, −0.62; 95% CI: (−1.20, −0.03); P=0.04; random-effects model] ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…El cuestionario recogía datos demográficos del estudiantado que accedió a participar en el estudio (edad y sexo) y datos académicos (grado, curso y universidad). El cuestionario POMS evalua, en escala Likert, 64 adjetivos que definen diferentes estados anímicos, para puntuar en 5 niveles (de 0 a 4) la frecuencia con la que se identifican las personas sondeadas con cada uno de esos estados de ánimo (Schichiri et al, 2016). Se trata de palabras seleccionadas por su capacidad para describir los sentimientos de las personas.…”
Section: Desarrollo De La Innovaciónunclassified
“…Moreover, gender differences are found in those hormones and the number and subsets of leucocytes and male are basically more SN dominance [23]. As for gender difference in psychological field, Shichiri K reported in detail [14] [24].…”
Section: Gender Differencementioning
confidence: 99%
“…The POMS is a widely used, reliable measure of emotional distress [9] [10]. Research shows that the POMS is reliable for Japanese participants [11] [12]; therefore, in this study, we used the Japanese version of the POMS [13] as we studied in advance [14].…”
Section: Profile Of Mood States (Japanese Version)mentioning
confidence: 99%